A case of swine flu superinfected with carbapenem resistant Klebsiella - Hazra, Rajdip; Manjunatha, SM; Manuar, Md. Babrak; Chakraborty, Sisir; Ghosh, Kaushik (Asian Journal of Medical Sciences, 2014)
Swine flu is caused by antigenic shift of influenza A virus with clinical features similar to seasonal influenza virus. Majority of the morbidity and mortality due to swine flu are attributable to pneumonia and the acute respiratory distress syndrome (ARDS). Bacterial superinfection can occur, though it is rare in adults. Here we report a case of swine flu superinfected with carbapenem resistant Klebsiella, which is often coined as Klebsiella ‘superbug’. Asian Journal of Medical Science, Volume-5(3) 2014: 120-122 http://dx.doi.org/10.3126/ajms.v5i3.8589